Answer:
(d) negative 12 s squared + 11 s t minus 2 t squared is the PRODUCT.
Explanation:
Here, the given expression is:
(negative 3 s + 2 t)(4 s minus t) = (- 3s + 2t) (4s - t)
Now, by DISTRIBUTIVE PROPERTY:
A(B-C) = AB - AC
Simplifying the given expression ,we get:
![(- 3s + 2t) (4s - t) = -3s(4s-t) + 2t(4s -t)\\= -3s(4s) -3s(-t) + 2t(4s) + 2t(-t) = -12s^2 + 3st + 8 st - 2t^2\\= -12s^2 + 11st - 2t^2\\\implies (- 3s + 2t) (4s - t) = -12s^2 + 11st - 2t^2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/i60zkcs6rol0qiu1cit84kdex1khriyvfb.png)
Now, the resultant expression can also be written as
= negative 12 s squared + 11 s t minus 2 t squared.
Hence, the option (4) is the correct option.